If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 + -1(4z + -9) = 8 + -5z Reorder the terms: 9 + -1(-9 + 4z) = 8 + -5z 9 + (-9 * -1 + 4z * -1) = 8 + -5z 9 + (9 + -4z) = 8 + -5z Combine like terms: 9 + 9 = 18 18 + -4z = 8 + -5z Solving 18 + -4z = 8 + -5z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '5z' to each side of the equation. 18 + -4z + 5z = 8 + -5z + 5z Combine like terms: -4z + 5z = 1z 18 + 1z = 8 + -5z + 5z Combine like terms: -5z + 5z = 0 18 + 1z = 8 + 0 18 + 1z = 8 Add '-18' to each side of the equation. 18 + -18 + 1z = 8 + -18 Combine like terms: 18 + -18 = 0 0 + 1z = 8 + -18 1z = 8 + -18 Combine like terms: 8 + -18 = -10 1z = -10 Divide each side by '1'. z = -10 Simplifying z = -10
| x^4/3-7x^2/3+10=0 | | 21+13x=9 | | 2.5x+-0.5x=13.5+4.5x | | 3p+9q-7(2p-8q)= | | 1(4x+2y)=1(-22) | | 3(y-9)=2(5+y) | | 2x+3xy-1=0 | | 5(1+4x)=5-4x | | 14z+122=-676 | | 9(n-1)-(-6n-8)=14n | | 40h-[24-(6h+8)-(5-2h)]=3-8h-12 | | 4*16/8+8+5-1+4 | | 0.13-0.02(x+1)=-0.03(3-x) | | -6a+42=10a+35 | | 22-13x=9 | | 6x+4-5x=0 | | 5y-23=-25+3y | | 250.00(h+15.00)=412.50 | | -9(-6+x)=-63 | | -6x^5+6x^4-2x^3=0 | | 165g=75 | | 11xy+2x=2 | | 250(h+15)=412.50 | | 85=21+4xs | | -3(3.3+8.9r)=6.1-24.7r | | n/15=1 | | (1-x)100=0.25 | | -4v/7=-20 | | 3(b+5y)=2(-5+4y) | | 5y-29=-31+4y | | 2(x-3)+7=10 | | (5/1)-(2(3a-4)/5)=(7-2a/2) |